The Influence of Kahoot! on Students’ Motivation and Learning Outcomes at SMAN 1 Percut Sei Tuan, Medan - Monica Junita Pangaribuan; Herbert Sipahutar (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
This study aims to determine the effect of using the interactive learning media Kahoot! on students’ motivation and learning outcomes at SMAN 1 Percut Sei Tuan, Medan. The research employed a quasi-experimental method with a pretest-posttest control group design. The sampling technique used was purposive sampling. The sample consisted of two classes: Class XI IPA 5 as the experimental group using Kahoot! and Class XI IPA 4 as the control group using conventional learning, each consisting of 35 students. The research instruments included a 34 item learning motivation questionnaire and a 30-item multiple-choice test. Data were analyzed using an independent samples t-test and linear regression analysis. The t-test results showed a significant effect (Sig. (2-tailed) = 0.001 < 0.05) on students’ motivation and learning outcomes in the experimental class. Furthermore, linear regression analysis showed that Kahoot! had a significant positive effect on students’ motivation, with regression coefficients of 0.839 and 0.693, and on learning outcomes, with coefficients of 0.869 and 0.862 (p < 0.05). Based on hypothesis testing and regression analysis, it can be concluded that the use of Kahoot! positively influences students’ motivation and learning outcomes at SMAN 1 Percut Sei Tuan, Medan.